Improving Nutritional Profile and Consumer Acceptance of Siomay Stuffing Through Integration of Mackerel Meat (Rastrelliger SP.) and Yellow Potato Flour (Solanum Tuberosum L.) - Sukoso, Sukoso; Kartikaningsih, Hartati; Ma’rifat, Tian Nur; Alif, Muhammad Rizki Mas (Jurnal Indonesia Sosial Sains, 2024)
Siomay, a popular Indonesian snack traditionally made with high-fat chicken or beef fillings, can be made healthier by using mackerel fish instead. This modification, combined with the addition of potato starch, aims to improve the nutritional profile of siomay while maintaining its appeal to consumers, as mackerel is both tasty and nutritious. This study aims to improve the nutritional profile and consumer acceptance of siomay filling through the integration of mackerel meat and potato starch. Data were analyzed using a Completely Randomized Factorial Design with two factors (mackerel meat and potato starch) mixed in different proportions in the siomay filling dough. Parameters tested included nutritional composition (protein, fat, carbohydrate, fiber, and mineral), physicochemical properties (texture, color, and aroma), and consumer acceptance test using a hedonic scale. The results showed that the most preferred treatment was K2D2 (14g mackerel meat and 20g potato starch), which was 5.6±1.5. The nutritional content of the siomay filling preferred by the panelists increased (water 29.07 g, protein 12.89 g, fat 3.65 g, ash 3.41 g, sugar 1.35 mg, vitamin B1 0.26 mg). However, the carbohydrate content decreased to 50.98 g, compared to the content of siomay filling without the addition of yellow potato starch (56, 74 g). This study shows that mackerel flour and potato starch can potentially be used to improve the nutritional profile and consumer acceptance of siomay filling.